Endophytic Paenibacillus polymyxa LMG27872 inhibits Meloidogyne incognita parasitism, promoting tomato growth through a dose-dependent effect - Singh, Richard Raj; Wesemael, Wim M. L. (Frontiers in Plant Science, 2022)
The root-knot nematode, Meloidogyne incognita, is a major pest in tomato production. Paenibacillus polymyxa, which is primarily found in soil and colonizing roots, is considered a successful biocontrol organism against many pathogens. To evaluate the biocontrol capacity of P. polymyxa LMG27872 against M. incognita in tomato, experiments were conducted both in vitro and in vivo. A dose-response effect [30, 50, and 100% (108 CFU/mL)] of bacterial suspensions (BSs) on growth and tomato susceptibility to M. incognita with soil drenching as a mode of application was first evaluated. The results show that the biological efficacy of P. polymyxa LMG27872 against M. incognita parasitism in tomato was dose-dependent. A significantly reduced number of galls, egg-laying females (ELF), and second-stage juveniles (J2) were observed in BS-treated plants, in a dose-dependent manner. The effect of P. polymyxa on tomato growth was also dose-dependent. A high dose of BSs had a negative effect on growth; however, this negative effect was not observed when the BS-treated plants were challenged with M. incognita, indicating tolerance or a defense priming mechanism. In subsequent in vivo experiments, the direct effect of BSs was evaluated on J2 mortality and egg hatching of M. incognita. The effect of BS on J2 mortality was observed from 12 to 24 h, whereby M. incognita J2 was significantly inhibited by the BS treatment. The effect of P. polymyxa on M. incognita egg hatching was also dependent on the BS dose. The results show a potential of P. polymyxa LMG27872 to protect plants from nematode parasitism and its implementation in integrated nematode management suitable for organic productions.